Localization of adaptive variants in human genomes using averaged one-dependence estimation - Lauren Alpert Sugden (Nature Portfolio, 2018)
Selective sweeps are events in which beneficial mutations spread rapidly through a population. Here, Sugden et al. develop SWIF(r), a probabilistic classification framework for detecting and localizing selective sweeps, and apply it to genomic data from the ‡Khomani San.